Reduced low frequency noise in electron beam evaporated MgO magnetic tunnel junctions - COEY, JOHN; FENG, JIA-FENG; DIAO, ZHU; KURT, HUSEYIN (My University, 2010)
We compare low frequency noise in magnetic tunnel junctions with MgO barriers prepared by electron-beam evaporation with those prepared by radiofrequency sputtering, both showing a high tunneling magnetoresistance. The normalized noise parameter in the parallel state of junctions with evaporated barriers is at least one order of magnitude lower than that in junctions with sputtered barriers, and exhibits a weaker bias dependence. The lowest normalized noise is in the 10(-11) mu m(2) range. A lower density of oxygen vacancies acting as charge trap states in the evaporated MgO is responsible for the lower noise.
PUBLISHED
Keywords: MAGNETICS; MAGNETORESISTANCE; Nanoscience & Materials